# Calculator search results

Formula
Solve the equation
Graph
$y = 2 \left ( 3 x - 1 \right )$
$y = 11 + \left ( 8 - x \right )$
$x$Intercept
$\left ( \dfrac { 1 } { 3 } , 0 \right )$
$y$Intercept
$\left ( 0 , - 2 \right )$
$x$Intercept
$\left ( 19 , 0 \right )$
$y$Intercept
$\left ( 0 , 19 \right )$
$2 \left( 3x-1 \right) = 11+ \left( 8-x \right)$
$x = 3$
 Solve a solution to $x$
$\color{#FF6800}{ 2 } \left ( \color{#FF6800}{ 3 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 1 } \right ) = \color{#FF6800}{ 11 } \color{#FF6800}{ + } \left ( \color{#FF6800}{ 8 } \color{#FF6800}{ - } \color{#FF6800}{ x } \right )$
 Organize the expression 
$\color{#FF6800}{ 6 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 2 } = \color{#FF6800}{ 19 } \color{#FF6800}{ - } \color{#FF6800}{ x }$
$6 x - 2 = \color{#FF6800}{ 19 } \color{#FF6800}{ - } \color{#FF6800}{ x }$
 Organize the expression 
$6 x - 2 = \color{#FF6800}{ - } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 19 }$
$\color{#FF6800}{ 6 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 2 } = \color{#FF6800}{ - } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 19 }$
 Organize the expression 
$\color{#FF6800}{ 6 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ x } = \color{#FF6800}{ 19 } \color{#FF6800}{ + } \color{#FF6800}{ 2 }$
$\color{#FF6800}{ 6 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ x } = 19 + 2$
 Organize the expression 
$\color{#FF6800}{ 7 } \color{#FF6800}{ x } = 19 + 2$
$7 x = \color{#FF6800}{ 19 } \color{#FF6800}{ + } \color{#FF6800}{ 2 }$
 Add $19$ and $2$
$7 x = \color{#FF6800}{ 21 }$
$\color{#FF6800}{ 7 } \color{#FF6800}{ x } = \color{#FF6800}{ 21 }$
 Divide both sides by the same number 
$\color{#FF6800}{ x } = \color{#FF6800}{ 3 }$
 그래프 보기 
Graph
Solution search results